Oilseed Meal Effects on the Emergence and Survival of Crop and Weed Species. (12th March 2012) - Rothlisberger, Katie L.; Hons, Frank M.; Gentry, Terry J.; Senseman, Scott A.
Abstract : Oilseed crops are being widely evaluated for potential biodiesel production. Seed meal (SM) remaining after extracting oil may have use as bioherbicides or organic fertilizers. Brassicaceae SM often contains glucosinolates that hydrolyze into biologically active compounds that may inhibit various pests. Jatropha curcas SM contains curcin, a phytoxin. A 14-day greenhouse study determined that Sinapis alba (white mustard), Brassica juncea (Indian mustard), Camelina sativa, and Jatropha curcas applied to soil at varying application rates [0, 0.5, 1.0, and 2.5% (w/w)] and incubation times (1, 7, and 14 d) prior to planting affected seed emergence and seedling survival of cotton [ Gossypium hirsutum (L.)], sorghum [ Sorghum bicolor (L.) Moench], johnsongrass ( Sorghum halepense ), and redroot pigweed ( Amaranthus retroflexus ). With each species, emergence and survival was most decreased by 2.5% SM application applied at 1 and 7 d incubations. White mustard SM incubated for 1 d applied at low and high rates had similar negative effects on johnsongrass seedlings. Redroot pigweed seedling survival was generally most decreased by all 2.5% SM applications. Based on significant effects determined by ANOVA, results suggested that the type, rate, and timing of SM application should be considered before land-applying SMs in cropping systems.